GAYA BERHIJAB HIJABIE COMMUNITY: (Studi Living Qur'an) - Ahmad Solahuddin (Institut Agama Islam Negeri (IAIN) Keiri, 2018)
Hijab or jilbab no longer hold to cover the aurat only, but also demanded an interesting aspect, beautiful and unique. Jilbab is no longer considered an ancient dress, but a fashion-able outfit. Muslimah who carries jilbab fashion was gathering and organizing in one community. One such community is the hijabie Community. As a community that must contest in the fashion market event, hijabie must have a unique 'style' from other communities. The uniqueness that emerged for example, Hijab style on which wearing a cowboy hat, not a helmet; or, Hijab style with Indian decoration; or, the style of hijab with the roof of a European house, etc. From this background, the authors will analyze the style of this community hijÄb hijabie using Pierre Bourdie's theory of taste. In the end, the results of this study are: 1. The mention of the name hijabie is built on the prestigious contained in the word hijab (Distinction) 2. Like hijabie, it can be called a domain because it is in the battle for domination between agencies. 3. Like members of the hijabie habitus in using hijab, they adhere to the Shafi'i school. This opinion is an opinion that is considered true because it becomes a general consciousness (doxa) 4. The capital that is in the realm of hijabie is symbolic capital owned by Atika, Economic Capital owned by Atika and Cultural Capital owned by Pipit, et al. People who have this capital are called agencies